2011
DOI: 10.4236/ns.2011.36068
|View full text |Cite
|
Sign up to set email alerts
|

Thermal response and optical absorptance of metals under femtosecond laser irradiation

Abstract: A detailed study on correlation between residual thermal response of a sample and its optical absorptance change due to laser-induced surface structural modifications in multi-shot femtosecond laser irradiation is performed. Experiments reveal an overall enhancement for residual thermal coupling and absorptance in air. Surprisingly, residual thermal coupling in air shows a non-monotonic dependence on pulse number and reaches a minimum value after a certain number of pulses, while these behaviors are not seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…As can be observed, with increasing sample roughness, sample heating increases. This is in agreement with [55,56]. In Fig.…”
Section: Discussionsupporting
confidence: 91%
“…As can be observed, with increasing sample roughness, sample heating increases. This is in agreement with [55,56]. In Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The confinement effects, energy coupling and shielding effects of environmental gas (hydrogen) significantly influence the ablation processes of Ge which is responsible for the dissimilar surface morphological modifications of Ge in two different environments. There are large number of research groups which have reported their work at such high pressure (10 −3 Torr) [18,19]. According to their results, first few pulses of laser are sufficient to remove contaminations from the surface of the irradiated target and following pulses cause real ablation [20].…”
Section: Methodsmentioning
confidence: 96%
“…After irradiating a surface with a femtosecond laser pulse, a fraction of the absorbed laser energy is retained in the surface layer of the sample and then dissipates into the bulk sample via heat conduction as residual thermal energy 31 32 . It has been determined that a significant amount of residual energy can be deposited in samples through surface roughness effects, exothermic chemical processes and ambient gas pressure effects 33 .…”
mentioning
confidence: 99%